The Media's Role in Globalizing Gayo Coffee: An Economic Communication Perspective Based on Islamic Values - Nabilah, Osha (Fakultas Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatullah Jakarta, 2024)
Using an economic communication approach based on Islamic values, this research investigates the role of the media in promoting Gayo coffee to the global market. Gayo coffee, originating from the highlands of Aceh, has long been considered one of the best coffees in the world. Despite this, local farmers face difficulties in gaining more global markets. The media plays a significant role in increasing awareness and demand at the global level through informative and positive reporting. Qualitative methods were used in this study, involving media content analysis and in-depth interviews with consumers, journalists and coffee entrepreneurs. Research shows that media coverage increases sales and prosperity of coffee farmers. Gayo coffee farming and marketing practices adopt Islamic values such as justice and sustainability, which increases the product's appeal in the global market. This study recommends synergy between farmers, government and media to maximize local economic potential through a more ethical and sustainable approach.